Physical Asset Development Planning of Langsat Park in Kebayoran Baru District - Damayanti, Adinda Fauziah (Jurnal Pariwisata Terapan, 2024)
The asset quality issues of Langsat Park consist of: 1) There are no pedestrian path for people with disabilities, doesn't have park identity signage and directional signs, and the parking area does not meet the criteria; 2) There are no outdoor fitness area and basketball court, the children's play area facilities are damaged; 3) There are no gazebos available, there are no toilets for people with disabilities; 4) Not equipped with CCTV and doesn't have disaster mitigation facilities. The research objective was to plan development of Langsat Park physical assets based on urban green spaces quality. The research method is descriptive with qualitative and quantitative approaches. Data collection techniques include observation, interviews, documentation studies. The results are development plan for 13 indicators of Langsat Park assets as follows: 1) Accessibility includes the demolition of pedestrian paths, construction of pedestrian paths and parking area, procurement of signages; 2) Functionality includes the construction of sports area, children’s play area, and procurement of sport facilities, children’s play facilities, seats, and vegetation; 3) Amenities includes the demolition toilets, the construction of gazebo and toilets, procurement of trash bin; 4) Safety includes the demolition of garden lights, procurement of garden lights, CCTV.